The hyl Efm gene in pHylEfm of Enterococcus faecium is not required in pathogenesis of murine peritonitis (2011)
Background Plasmids containing hyl Efm (pHylEfm) were previously shown to increase gastrointestinal colonization and lethality of Enterococcus faecium in experimental peritonitis. The hyl Efm gene, predicting a glycosyl hydrolase, has been considered as a virulence determinant of hospital-associated E. faecium, although its direct contribution to virulence has not been investigated. Here, we constructed mutants of the hyl Efm -region and we evaluated their effect on virulence using a murine peritonitis model. Results Five mutants of the hyl Efm -region of pHylEfmTX16 from the sequenced endocarditis strain (TX16 [DO]) were obtained using an adaptation of the PheS* system and were evaluated in a commensal strain TX1330RF to which pHylEfmTX16 was transferred by mating; these include i) deletion of hyl Efm only; ii) deletion of the gene downstream of hyl Efm (down) of unknown function; iii) deletion of hyl Efm plus down; iv) deletion of hyl Efm -down and two adjacent genes; and v) a 7,534 bp deletion including these four genes plus partial deletion of two others, with replacement by cat. The 7,534 bp deletion did not affect virulence of TX16 in peritonitis but, when pHylEfmTX16Δ7,534 was transferred to the TX1330RF background, the transconjugant was affected in in vitro growth versus TX1330RF(pHylEfmTX16) and was attenuated in virulence; however, neither hyl Efm nor hyl Efm -down restored wild type function. We did not observe any in vivo effect on virulence of the other deletions of the hyl Efm -region Conclusions The four genes of the hyl Efm region (including hyl Efm ) do not mediate the increased virulence conferred by pHylEfmTX16 in murine peritonitis. The use of the markerless counterselection system PheS* should facilitate the genetic manipulation of E. faecium in the future.